2016
DOI: 10.1002/2016ja022594
|View full text |Cite
|
Sign up to set email alerts
|

New modes and mechanisms of thermospheric mass density variations from GRACE accelerometers

Abstract: Monitoring and understanding the upper atmosphere processes is important for orbital decay and space physics. Nowadays, Low Earth Orbit (LEO) accelerometers provide a unique opportunity to study thermospheric density variations with unprecedented details. In this paper, thermospheric mass densities variations from Gravity Recovery and Climate Experiment (GRACE) accelerometers are investigated for the period 2003–2016 using the principal component analysis (PCA). The resulting modes are analyzed and parameteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…Meanwhile, Figs. 6 and 13 in Calabia et al (2016) also show that two maxima peaks are depicted in June in the Northern Hemisphere, but only one in December in the Southern Hemisphere. However, the underlying physical processes for this feature need further investigation.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Meanwhile, Figs. 6 and 13 in Calabia et al (2016) also show that two maxima peaks are depicted in June in the Northern Hemisphere, but only one in December in the Southern Hemisphere. However, the underlying physical processes for this feature need further investigation.…”
Section: Resultsmentioning
confidence: 98%
“…These results illustrate that the thermospheric annual asymmetry should be associated with the varying Sun-Earth distance. Actually, previous studies suggested that the difference of solar radiation associated with the difference of Sun-Earth distance between June and December would contribute to the annual asymmetry (Qian et al, 2012;Lei et al, 2013Lei et al, , 2016Emmert, 2015;Calabia et al, 2016). Moreover, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nondrag terms can be modeled, fixed, and then deducted from the measurements by using prior procedures in terms of navigational information, spacecraft records, and empirical models (e.g., Tolson et al, 2005Tolson et al, , 2007Tolson et al, , 2008. Subsequently, the aerodynamic acceleration a aero is used to derive the atmospheric mass density as follows (e.g., Calabia & Jin, 2016;Tolson et al, 2005;Keating et al, 2008;Jin et al, 2018):…”
Section: Atmospheric Mass Density From Acc-measured Accelerationmentioning
confidence: 99%
“…In this paper, we standardize the data into several reference altitudes of 10 km intervals in the vertical directions. The normalization equation is as follows (Calabia & Jin, 2016): & Millour, 2009;González-Galindo, Forget, Lpez-Valverde, & Angelats i Coll, 2009). In order to maintain consistency between the measurements and the MCD, the scenarios that reflect the surface dust and solar activities should be set properly based on Millour et al (2015) and Montabone et al (2015).…”
Section: Density Normalization With Reference Modelmentioning
confidence: 99%